The Effect of Customer Relationship Management on Customer Loyalty at PT BRI Cibinong Branch - Amel, Nada Shafa; Mulyati, Heti; Aminah, Mimin (Jurnal Manajemen, 2023)
The banking sector has an influence on the economy of a country. Service quality is the main requirement that determines the success of banking as a company engaged in service providers. Bank BRI Cibinong is one of BRI's branch offices in Cibinong District. The main goal of the banking business is to make enormous profits so that the company can survive. One of BRI's initiatives to cultivate long-term relationships with customers is to create customer satisfaction through responsiveness in answering customer complaints. Customer loyalty is a valuable company asset that must be maintained and is an absolute must for Bank BRI to exist and win the competition. The key performance indicator (KPI) of BRICare Cibinong Branch demonstrates that most of the customer complaints reports have not passed the 90 percent standard of assessment. The goal of this study is to analyze the factors that influence customer satisfaction through customer relationship management (CRM) and their impact on customer loyalty. Descriptive analysis and Covariance Based-Structural Equation Modeling (CB-SEM) were used as analytical methods. CRM variables including complaint handling, cross selling, technology adoption and customer appreciation have a positive impact on customer satisfaction. The complaint handling variable has the biggest coefficient value in creating customer satisfaction.